Differences in the effects of square stepping exercise and Otago exercise on dynamic balance based on body mass index in the elderly - Wijianto; Muchsin Doewes; M. Furqon Hidayatullah; Febriani Fajar Ekawati (Physical Therapy Journal of Indonesia, 2026)
Background: The increasing elderly population in Indonesia face higher risks of balance disorders and falls, threatening independence. Exercise interventions, such as strength and balance training, can improve dynamic balance. This study aimed to analyze the differences in dynamic balance improvement between square stepping exercise and Otago exercise in older adults based on body mass index (BMI). Methods: The sample was randomly divided into two groups: square stepping exercise (SSE group) and Otago exercise (OT group). Dynamic balance was assessed using the timed up and go (TUG) test, conducted before and after the intervention. This study used a 2×3 factorial experimental design with purposive sampling. Older adults aged 60–75 years with good cognitive and walking ability were included, while those with sensory impairments, mobility limitations, or lower extremity disorders were excluded. Sixty eligible participants were randomly assigned to either the SSE group (n = 30) and the OT Group (n = 30). Data were analyzed using a 2×3 factorial ANOVA, with statistical significance set at p < 0.05. Results: This study found that both SSE and OT interventions significantly improved dynamic balance in older adults, as measured by pre- and post-intervention TUG test. Both groups showed reduced TUG test times: the OT group from 13.76 to 11.84 seconds, and the SSE group from 14.48 to 11.13 seconds. ANOVA analysis indicated that the type of exercise significantly affected dynamic balance (F(1.54) = 4.515; p=0.038), while BMI and its interaction showed no significant effect (p> 0.05). Conclusion: Both exercises improved dynamic balance in older adults. However, the SSE group showed greater effectiveness than the OT group. Exercise type significantly influenced balance outcomes, while BMI had no significant effect.